2001
DOI: 10.1021/jf0105541
|View full text |Cite
|
Sign up to set email alerts
|

Automated Strong Cation Exchange Extraction of Fatty Acid Esters of 3-(N-Phenylamino)-1,2-propanediol from Oil Samples for Routine Quantification by HPLC-APCI/MS/MS

Abstract: Fatty acid esters of 3-(N-phenylamino)-1,2-propanediol are currently considered the best chemical markers of toxic oils related to the Spanish toxic oil syndrome. Recent research in this area has undertaken the exhaustive and quantitative characterization of these compounds in oils collected during the epidemic outbreak. Current methods developed in this laboratory are based on solid phase extraction (SPE) using SCX cartridges followed by HPLC-APCI/MS/MS quantification. To circumvent the long and tedious extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Owing to the complexity of the oil extract and the low concentrations at which PAPs are found, a preconcentration technique based on SCX was applied. This technique, developed by Calaf et al ,14, 15 had demonstrated to be very efficient in improving the detection limits of the minor amine‐containing compounds in oils 14. In addition, the fraction of volatile compounds recovered from the chemical reactor was also analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Owing to the complexity of the oil extract and the low concentrations at which PAPs are found, a preconcentration technique based on SCX was applied. This technique, developed by Calaf et al ,14, 15 had demonstrated to be very efficient in improving the detection limits of the minor amine‐containing compounds in oils 14. In addition, the fraction of volatile compounds recovered from the chemical reactor was also analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…An approximation to the relative proportions of representative compounds in the oil samples studied here calculated relative to the concentration of oleanilide (OA), the most abundant aniline derivative in oil, shows that except for the major FAAs (oleyl or linoleyl anilides) and a few PAPs, all other known aniline derivatives were found at concentrations lower than 0.4%. Quantitative details on the analysis of over 2600 samples over a two‐year period have been reported in the literature 14, 15. The majority of these samples contained OA at 8–100 ppm 14…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations